TREM-1 as a potential gatekeeper of neuroinflammatory responses: therapeutic validation and mechanistic insights in experimental traumatic brain injury - Zhang, Yunsheng; Zhang, Yulian; Dang, Hanhan; Zhang, Chuanpeng; He, Kun; Yang, Xu; Wang, Zixi; Zhang, Li; Yu, Yanbing (Frontiers in Immunology, 2025)
BackgroundTraumatic brain injury (TBI) triggers a cascade of neuroinflammatory responses mediated by microglial activation, which significantly contributes to secondary brain damage. While triggering receptor expressed on myeloid cells-1 (TREM-1) is a key inflammatory amplifier, its mechanistic role and therapeutic potential in TBI remain elusive. Thus, this study endeavored to elucidate the exact role of TREM-1 in experimental TBI.MethodsA controlled cortical impact (CCI) model was established in male C57BL/6 mice to induce TBI. The temporal expression profile of TREM-1 was assessed using RNA sequencing and Western blot (WB). The TREM-1 inhibitory peptide LP17 was administered intranasally at 2 hours post-injury (hpi). Neurobehavioral assessments, histological analyses, immunofluorescence (IF), brain water content (BWC) measurement, Evans blue (EB) assays and laser speckle contrast imaging (LSCI) were performed in this study. In vitro experiments using BV2 microglial cells were conducted to investigate the molecular mechanisms underlying TREM-1-mediated inflammation. Spleen tyrosine kinase (SYK) inhibition was achieved using R406, and TREM-1 small interfering RNA (siRNA) and overexpressing plasmids were performed to validate its role in NF-κB signaling and pyroptosis quantified using WB and enzyme-linked immunosorbent assay (ELISA). Quantitative data are expressed as mean ± SD, and group comparisons were made by two-tailed Student’s t-tests or one-way ANOVA with Tukey’s post hoc test, with P < 0.05 considered statistically significant.ResultsTBI significantly upregulated TREM-1 expression in microglia, peaking at 3 days post-injury (dpi). Intranasal administration of the TREM-1 antagonist LP17 treatment attenuated neuroinflammation, reduced blood-brain barrier disruption, ameliorated cerebral blood flow decrease, promoted synaptic remodeling, and improved functional outcomes. Mechanistically, through its interaction with SYK, TREM-1 triggered the CARD9/NF-κB signaling and induced pyroptosis. SYK inhibition reversed these effects, confirming the necessity of the TREM-1/SYK axis in neuroinflammatory signaling. In vitro studies further demonstrated that TREM-1 overexpression enhanced SYK phosphorylation, NF-κB activation, and pyroptosis, while LP17 or R406 treatment suppressed these responses.ConclusionOur finding demonstrates that TREM-1 critically mediates neuroinflammation and synaptic dysfunction after TBI. Pharmacological targeting of TREM-1 attenuates neuroinflammation, reduces cerebral edema, preserves blood-brain barrier integrity, and improves functional recovery. These effects are mediated through suppression of TREM-1-dependent NF-κB signaling and pyroptosis. These results highlight TREM-1 as a promising therapeutic target for TBI.